Mechanical properties of fine grained hardmetals produced by pressureless and pressure assisted sintering technologies. (31st October 2015) - Zivcec, M.; Broeckmann, C.; Hajeck, M.; Rödiger, K.
Abstract : Pressureless sintering and the two pressure assisted sintering technologies – sintering + hot isostatic pressing (sinter-HIP) and field assisted sintering technology (FAST) were used to produce a fine grained WC-6 Co hardmetal. In order to compare the mechanical properties of the hardmetals, which result from different sintering technologies, the material strength was determined. In the present study the uniaxial three point bending test and the biaxial ball on three balls test were used as strength measuring methods. The results were described by the Weibull distribution function. Additionally, the paper will analytically compare the two tests by describing the relation of the strength of the samples to their effective volumes. Based on this procedure components having arbitrary shapes and volumes can be designed.